2019
DOI: 10.1088/1361-6501/ab2419
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing multi-GNSS time and frequency transfer using a refined stochastic model of a receiver clock

Abstract: The precise point positioning (PPP) technique has been widely used for remote time and frequency transfer. With the development of the multiple global navigation satellite system (multi-GNSS), the PPP technique with multi-GNSS has been studied in order to improve the performance of time and frequency transfer. However, the day boundary problem, model correction residuals, and noise may affect the clock estimation in multi-GNSS PPP. In this study, we refine the receiver clock parameter using a stochastic model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Daqian et al [24] verified the PPP time transfer performance through experiments using real-time products of cutaneous nerve entrapment syndrome analysis centers, revealing that the standard deviation under multi-system observations and GPS ambiguity fixing technology was the smallest. Daqian et al [25] proposed a always modeling method to reduce the additional noise in the clock estimation process, and proposed a clock initialization method to solve the daily boundary problem, thereby improving the stability of time transfer.…”
Section: Introductionmentioning
confidence: 99%
“…Daqian et al [24] verified the PPP time transfer performance through experiments using real-time products of cutaneous nerve entrapment syndrome analysis centers, revealing that the standard deviation under multi-system observations and GPS ambiguity fixing technology was the smallest. Daqian et al [25] proposed a always modeling method to reduce the additional noise in the clock estimation process, and proposed a clock initialization method to solve the daily boundary problem, thereby improving the stability of time transfer.…”
Section: Introductionmentioning
confidence: 99%
“…With the completion of BDS-3 global networking, it brings a great opportunity for time transfer [29]. Moreover, Lyu et al [30] added the receiver clock model for PPP time transfer, where they indicated that the method could solve the phenomenon of day boundary.…”
Section: Introductionmentioning
confidence: 99%